Characterizing Senna Alata Fiber and Echinochloa Frumentacea Leaf Fiber: A Novel Approach for Composite Applications - Shalom, N. (Recent Research Reviews Journal, 2023)
The characterization of natural fibres is used in the domain of materials science and engineering with the objective of generating new environmentally acceptable bio-composites. The purpose of this study is to create and characterize a bio-composite reinforced with Senna Alata fibre and Echinochloa frumentacea fiber. This study analyzes the mechanical, thermal, and morphological characteristics of the fibre. The physicochemical research indicated that the fibre has an excellent average density of 1270 kg/m3. In fact, Senna Alata Fiber (SAF) tensile strength ranges from 2300 to 5479 MPa and Echinochloa frumentacea leaf fiber -EFLFs tensile strength ranges from 204.32 14.25 MPa. As a result, the current study suggests that SAF and EFLF can be used as reinforcing materials with maximum specific characteristics as well as minimal environmental impact in the manufacturing of bio- composite.
Keywords: Senna Alata Fiber; Echinochloa frumentacea leaf fiber; automotive; bio-composites; reinforcement; characterization